2016
DOI: 10.1016/j.aca.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to antimony film screen-printed electrodes using carbon-based nanomaterials substrates

Abstract: Three different commercial carbon nanomaterial-modified screen-printed electrodes based on graphene, carbon nanotubes and carbon nanofibers were pioneeringly tested as electrode platforms for the plating with Sb film. They were microscopically and analytically compared to each other and to the most conventional unmodified carbon screen-printed electrode (SPCE). The obtained detection and quantification limits suggest that the in-situ antimony film electrode prepared from carbon nanofibers modified screen-print… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 16 publications
4
44
1
Order By: Relevance
“…Seed mediated approach synthesis of nanostructures is a multistep methodology [23] based on the first fast crystallization of nanoseeds, which can be used for further nucleation and customized growth of shape defined nanoprisms of larger size [24]. TEM characterization of spherical Ag-nanoseeds (Figure 2A,B) and shaped defined Ag-nanoprisms (Figure 2C,D) provides valuable morphological information of the materials incorporated to SPCNFE matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Seed mediated approach synthesis of nanostructures is a multistep methodology [23] based on the first fast crystallization of nanoseeds, which can be used for further nucleation and customized growth of shape defined nanoprisms of larger size [24]. TEM characterization of spherical Ag-nanoseeds (Figure 2A,B) and shaped defined Ag-nanoprisms (Figure 2C,D) provides valuable morphological information of the materials incorporated to SPCNFE matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of peptide modified SPEs was based on a two-step procedure previously described [19] with slight modifications (Figure 1). A carbon nanofiber modified screen-printed electrode (SPCNFE) was considered as a platform for electrode modification, since it has been reported that its much larger effective surface area provides sensors with a better analytical performance [19][20][21] 2.3.1.1. Diazonium salt electrografting.…”
Section: Preparation Of Modified Spesmentioning
confidence: 99%
“…The Zn(II), Cd(II), and Pb(II) concentrations employed were 89.2 μg/L (simultaneously), as all three analytes were within the linear concentration range for all three 0.6Bi0.4Sb_0.5_mg/L, 0.1Bi0.9Sb_1.0_mg/L, and 0.0Bi1.0Sb_0.5_mg/L combinations at t acc =60 s. In general, the longer the t acc , the more analyte is deposited and a higher stripping signal is expected. Moreover, it was reported previously that by using BiFE, SbFE, and Bi−SbFE and employing longer t acc better analytical performances for heavy metal determination were obtained , . The stripping signal of the three analytes (Δ i ) was plotted vs. t acc , as shown in Figure (one of the three replicates is given).…”
Section: Resultsmentioning
confidence: 99%
“…SbFE was also applied ex situ for heavy metal detection . Different materials were reported as a working electrode platform for SbFE, e. g. screen‐printed electrodes (SPE) , different nanomaterial‐modified SPEs , different carbon‐ and metal‐based substrates (gold and platinum disk electrodes and a carbon fibre microelectrode ) and carbon paste electrodes . Urbanova et al.…”
Section: Introductionmentioning
confidence: 99%